Foreword - Šteinberga, Airisa (History of Engineering Sciences and Institutions of Higher Education, 2024)
The eighth scientific journal, prepared by RTU Research Centre for Engineering History (RCEH), is published in the year of the 162nd Anniversary of Riga Technical University (RTU). It comprises five scientific articles, the authors of which are scientists and lecturers of universities in Latvia, North Macedonia, and Germany, as well as a member and student of the Latvian Association for the History of Science.